Dysregulation of Systemic and Mucosal Humoral Responses to Microbial and Food Antigens as a Factor Contributing to Microbial Translocation and Chronic Inflammation in HIV-1 Infection - Hel, Zdenek; Xu, Jun; Denning, Warren L; Helton, E Scott; Huijbregts, Richard P H; Heath, Sonya L; Overton, E Turner; Christmann, Benjamin S; Elson, Charles O; Goepfert, Paul A; Mestecky, Jiri (PLOS pathogens, 2017)
HIV-1 infection is associated with an early and profound depletion of mucosal memory CD4+ T cells, a population that plays an indispensable role in the regulation of isotype switching and transepithelial transport of antibodies. In this study, we addressed whether the depletion of CD4+ T cell in HIV-1-infected individuals results in altered humoral responses specific to antigens encountered at mucosal surfaces. Comprehensive protein microarray of systemic humoral responses to intestinal microbiota demonstrated reduced IgG responses to antigens derived from Proteobacteria and Firmicutes but not Bacteroidetes. Importantly, intestinal secretions of antiretroviral therapy-treated HIV-1-infected individuals exhibited a significant elevation of IgM levels and decreased IgA/IgM and IgG/IgM ratios of antibodies specific to a variety of microbial and food antigens. The presented findings indicate reduced competence of mucosal B cells for class switch recombination from IgM to other isotypes limiting their capacity to react to changing antigenic variety in the gut lumen. Decreased availability of microbiota-specific IgA and IgG may be an important factor contributing to the translocation of microbial antigens across the intestinal mucosal barrier and their systemic dissemination that drives chronic inflammation in HIV-1-infected individuals.
Keywords: Intestinal Mucosa; Immunity, Humoral; zánět; imunoglobulin G; imunoglobulin A; Food; HIV Infections; HIV-1; lidé; Antigens; antigeny; Immunoglobulin A; Microbiota; Immunoglobulin G; HIV infekce; Inflammation; přesmyk imunoglobulinových tříd; Humans; regulace genové exprese; mikrobiota; humorální imunita; B-Lymphocytes; Immunoglobulin Class Switching; B-lymfocyty; chronická nemoc; CD4-Positive T-Lymphocytes; Gene Expression Regulation; Chronic Disease; potraviny; střevní sliznice; CD4-pozitivní T-lymfocyty